Peningkatan Hasil dan Motivasi Belajar Pendidikan Agama Islam Menggunakan Metode Pembelajaran Praktik Siswa Kelas IV SDN 1 Pengkelak Mas - Syawal, Syawal (khatulistiwa, 2020)
The aim of this study; First, the level of application of practical learning methods; students' learning motivation before and after the practical learning method was applied; student learning outcomes before and after the application of practical learning methods. The second is to determine the effect of applying practical learning methods on students' motivation and learning outcomes. This research was conducted at SDN 1 Pengkelak Mas, Pengkelak Mas sub-district, West Sakra sub-district, East Lombok district. The method used in experimental quantitative research. The sample in this study was fourth-grade students. The research instrument used an observation sheet, a questionnaire/questionnaire, and a skill/psychomotor assessment test. Data analysis technique using t-test. The results of the study: First, the level of application of the practical learning method in the very good category, the level of student learning motivation before the application of the practical learning method was in the very high category, and after the application of the practical learning method in the very high category; student learning outcomes before applying the high category practical learning method, after applying the very high category practical learning method. Second, there is the effect of applying practical learning methods on learning motivation and student learning outcomes.